Turning land into capital development and dispossession in the Mekong region - Hirsch, Philip 1957-; Woods, Kevin; Scurrah, Natalia; Dwyer, Michael B. (University of Washington Press, 2022)
Introduction : Turning Land into Capital / Philip Hirsch, Kevin Woods, Natalia Scurrah and Michael Dwyer -- Land and Capital across Borders : A Regional Geopolitics / Natalia Scurrah and Philip Hirsch -- Legacies in Land Governance : Colonialism, War and Socialism / Kevin Woods, Michael Dwyer and Jean-Christophe Diepart -- Agrarian Modernization and Counter-Land Reforms : Ideologies and Realities / Jean-Christophe Diepart and Christian Castellanet -- Grounding Land Justice : Contested Principles, Processes and Outcomes / Carl Middleton and Vanessa Lamb -- Land Commodification, State Formation, and Agrarian Capitalism : The Political Economy of Land Governance in Cambodia / Jean-Christophe Diepart and Carl Middleton -- "Thirty Thousand Hectares Will Not Be a Problem" : The Politics of Large-Scale Land Development in Laos / Michael Dwyer -- Legacies of Race, Ethnicity, and War : Contemporary Land Governance Reform in Myanmar / Kevin Woods -- Movement, Counter-Movement, and Regionalization of Capital : The Dynamics of Land Relations in Thailand / Philip Hirsch -- Land from the Tiller : The Politics of "Land Recovery" in Vietnam / Nga Dao and Marie Mellac -- Conclusion : A Regional Approach to Land Capitalization / Philip Hirsch, Kevin Woods, Natalia Scurrah and Michael Dwyer.
Includes bibliographical references and index
Keywords: Bodenpolitik; Geopolitik; Bodenrecht; Landwirtschaftliche Entwicklung; Wirtschaftsliberalismus; Bodenreform; Enteignung; Soziale Folgen; Mekong; Kambodscha; Laos; Myanmar; Thailand; Vietnam; Land use, Rural / Economic aspects / Mekong River Valley; Rural development / Mekong River Valley; Agriculture / Economic aspects / Mekong River Valley; Land reform / Economic aspects / Mekong River Valley; Economic development / Mekong River Valley; Agriculture and state / Mekong River Valley; Aufsatzsammlung; Fallstudiensammlung